Pengaruh Paparan Polutan Udara Terhadap VO2Max pada Pekerja Batik di Lingkungan Pabrik Batik - Hafidzah, Farah (Jurnal Kedokteran Indonesia, 2009)
Background: Batik industry uses basic materials that contains wax. Wax will produce smoke whenheated. Smoke of wax contains pollutants such as NOX, SO2, CO, CO2, HC, H2S and particles. Thepollutants can cause acute or chronic damage to lung tissue if inhaled by the workers, depending onthe pollutant concentration, duration of exposure and vulnerability of the body. The purpose of thisstudy is to determine the effect of air pollutants on V2max to batik workers in batik factory environment.Methods: This study used an analytical cross sectional study using fixed exposure sampling techniqueconducted in July 2010. The sample consisted 60 batik factory workers both inside and outside thefactory plant. Data were collected by use of questionnaire and the shuttle run test. The data wereanalyzed using multiple linear regression on SPSS version 16 and Stata Intercooled version 7.Results: The results showed that VO2max of batik factory workers was 3.9 mL / kg / minute lower thanthat of workers outside the factory batik (b =- 3.9, p = 0.003) after controlling for the effect of smokinghabits, age, length of employment, and BMI.Conclusions: Working at batik factory significantly reduces VO2max by 3.9 mL/kg minute after controllingfor smoking, age, length of employment, and BMI.Keywords: air pollutant, VO2max, batik factory